2018
DOI: 10.1037/cap0000164
|View full text |Cite
|
Sign up to set email alerts
|

The new Caucus-race: Methodological considerations for meta-analyses of psychotherapy outcome.

Abstract: The Dodo Bird Verdict (DBV)-the proposition that all psychotherapies are equally effective-remains bitterly contested by researchers, who have mainly used meta-analyses as the primary tool to adjudicate the disagreements about relative psychotherapy efficacy. However, the meta-analytic literature remains inconclusive and contradictory, due in part to heterogeneity in researchers' methodological and statistical decisions. We undertake a review of a number of recent meta-analyses of psychotherapy outcomes to hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
(125 reference statements)
0
3
0
Order By: Relevance
“…This hypothesis is inconsistent with our results. Assertions about the predominant role of common psychotherapy factors have been criticized because they are often based on the findings of meta‐analyses that aggregate very different disorders (e.g., Sanders & Hunsley, 2018). There is no question that a sound working alliance is a necessary condition for effective psychotherapy, including CBT (e.g., Beck et al, 1985; Castonguay & Beutler, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is inconsistent with our results. Assertions about the predominant role of common psychotherapy factors have been criticized because they are often based on the findings of meta‐analyses that aggregate very different disorders (e.g., Sanders & Hunsley, 2018). There is no question that a sound working alliance is a necessary condition for effective psychotherapy, including CBT (e.g., Beck et al, 1985; Castonguay & Beutler, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…To generate a pool of RCTs that could be paired, we reviewed the reference sections of studies that had meta‐analysed treatment comparison studies. Both Sanders and Hunsley (2018) and Wampold and Imel (2015) reviewed such meta‐analyses. These reviews along with a search of PsycINFO and the Publicly Available Content Database on 5 May 2019 using the search terms ‘meta‐analysis of comparative outcome studies’, ‘meta‐analysis of direct comparisons’ and ‘therapy versus therapy meta‐analysis’ were used to identify relevant meta‐analyses.…”
Section: Matching Pairs Of Studies and Coding Outcomesmentioning
confidence: 99%
“…Researchers have examined it from every angle and have demonstrated that it has positive effects on mental health, and can reduce the economic burden of mental illness (American Psychological Association, 2013; Australian Psychological Society, 2010; Fansi, Jehanno, Lapalme, Drapeau, & Bouchard, 2016; Hunsley, Elliott, & Therrien, 2014; Vasiliadis, Dezetter, Latimer, Drapeau, & Lesage, 2017), while many psychologists and other clinicians have made it the core of their clinical practice (Hunsley, Ronson, & Cohen, 2013; Ionita & Fitzpatrick, 2014). The November 2018 issue of Canadian Psychology , which was entirely dedicated to psychotherapy, illustrates the richness of the literature on psychotherapy, with papers that discuss such critical issues as the need for publicly funded psychotherapy and for greater access to psychotherapy, including in remote areas, the importance of self-care and of well-being amongst therapists, change and improvement with psychotherapy, the economic implications of offering therapy, the legal and ethical considerations related to treating specific populations, differences between various groups of practitioners, or the strengths and weaknesses of the methods used to examine the efficacy of therapy (Gajic-Veljanoski et al, 2018; Jimenez-Arista, Tracey, & Levy, 2018; Kalegeropoulos, Roquet, Sztopa, Bradley, & Drapeau, 2018; Laverdière, Kealy, Ogrodniczuk, & Morin, 2018; Lints-Martindal, Carlson, Goodwin, & Thompson, 2018; Maranzan et al, 2018; Mathews, 2018; McPhail, Stephens, & Heasman, 2018; Sanders & Hunsley, 2018; Tasca, Town, Abbass, & Clark, 2018). More importantly perhaps, psychotherapy has also recently received attention from policymakers.…”
mentioning
confidence: 99%